Comparative evaluation of healing after surgical excision of oral mucosal lesions using PRF and collagen membrane - Poddar Vishal Kumar; Arora Srimathy S.; Kumari Kusum (EDP Sciences, 2023)
Objectives The purpose of the comparative study was to evaluate the clinical parameters affecting healing after surgical excision of superficial, potentially malignant oral lesions using Platelet Rich Fibrin (PRF) and Collagen Membrane. Material and methods: A total of 100 patients requiring treatment for oral mucosal lesions (OML) were enrolled through a randomized selection of two different groups, where Group 1 (50 patients) received PRF while Group 2 (50 patients) received Collagen membrane following excisional biopsy. Parameters checked were Pain, Clinical Healing, Granulation Tissue, Epithelialization, Wound Contracture, and Complications postoperatively at 3rd, 7th and 30th day. Results: Group 1 showed better results with post-operative pain, clinical healing and granulation presence when compared to Group 2. Conclusion: PRF can be ascertained as a better dressing material than Collagen Membrane with better healing potential.